Influence on the financial stability of the construction company trends of business activity in the construction industry - Molodid, O.; Kharchenko, R. (Ways to Improve Construction Efficiency, 2018)
The article defines the formation of management of the development of financial stability of the construction company. The author concludes that in order to increase the financial stability of the construction company there is an acceleration of turnover of working capital at the stage of creation of production stocks. Increasing the financial stability of the construction company will contribute to an increase in the share of the main sources of formation of stocks and costs in the total amount of sources of funds.